Changes in peripheral blood cell subpopulations in elite kayakers during a training season - Borges, G. F.; Rama, L.; Alves, F.; Pedreiro, S.; Paiva, A.; Teixeira, A. M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Prolonged strenuous exercise has been associated with a depression of immune function. The aim of this study was to investigate if changes in training load could affect peripheral blood leukocyte counts and percentage, including B, T, TCD4+, TCD8+ and Natural Killer (NK) lymphocytes in elite kayakers during a training season. Methods: The sample comprised 8 male elite canoeists, 22±4.0 years old, 78.5 ±6.9kg body mass and 178.0±5.6cm stature. The control group were 6 health males, 18.1±5.0 years old, 73.0± 6.6kg body mass and 172.5±4.6cm stature. Blood samples were collected at different moments of the training season: at the beginning, after an off training period of 6 weeks (t0), at the 11th week after the application of high weekly training volumes (t1), at week 26 after a cycle of intense training (t2), at the 31th week at the end of a tapering phase (t3). Blood samples were collected from the non-athlete group at 3 time points: t1 early November, t2 late February and t3 early April. Lymphocyte subpopulations were determined by flow cytometry (FACSCalibur; BD, USA). Statistical analysis was done using ANOVA. Significance was set at P<0.05. Results: At the time of increased training volume (t1) granulocytes counts decreased and remained lower until the end of the training season. The number of lymphocytes decreased at the time of higher intensity training (t2) but recovered to baseline values at t3. On the other hand no changes were for the lymphocyte subpopulations between baseline and the other time points, except for the CD3+CD56+CD8+ subpopulation that showed an increase at t2 and t3. However, at the end of the tapper period (t3) total cell numbers in the CD3+, CD3+CD4+, CD3+CD8+, CD3+CD8- CD4-, CD3-CD19+, CD3-CD56+, CD3-CD56+CD8- and CD3-CD56+CD8+ subpopulations increased when compared to t1. No differences for the non-athletes were observed between the time points studied. At the beginning of the training season, both CD3+ and NK cell counts were lower in the kayakers than in the non-athletes. Discussion: Our data suggests that increased training load leads to a decrease in lymphocyte counts at the periods of high training loads. When compared to the non-athlete group, lymphocyte numbers were lower in the kayakers at t0, t1 and t2. Although not significant we see a decrease in all the lymphocyte counts subpopulations when volume reaches it`s highest values (t1). When the training season reaches the high intensity phase (t2) values are already increasing and will do so until the end of the season. Periods of heavy training have been associated with immune depression (1) normally reversible by a tapering period.